Captain Wardiman's Way of Fighting the Dutch - Matanasi, Petrik (History Education, University of Jember, 2023)
We traced the life of Captain Wardiman which has not been much discussed in Indonesian historical research. Captain Wardiman was one of the leading Javanese officers in the Dutch East Indies era. He is actually an interesting figure in the history of Indonesians in the Dutch East Indies colonial army. Captain Wardiman was considered brilliant in suppressing the East Kalimantan SI Pasir rebellion. He actually left Dutch military service when his income was high. He wanted to be a soldier again when Indonesia faced the Dutch army. Keywords: Captain Wardiman’s, figthting, Dutch